Thermoeconomic and impact assessments of trigeneration systems with various fuels - Sorgulu, Fatih; Dincer, Ibrahim (ELSEVIER SCI LTD, 2022)
In this paper, both renewable hydrogen production and blending with natural gas for the existing distribution pipelines are studied through a unique trigeneration systems development, analysis, and assessment. A comparison with various conventional fuels, such as diesel, coal, biogas, and biodiesel is provided. In this regard, solar and wind energy-based power systems integrated with reverse osmosis units are designed and compared in energy, exergy, environment, and cost. Solar PV panels and wind turbines are considered for electricity generation. For hydrogen-based systems, an electrolyzer is utilized to produce hydrogen. The heat demands needed for residential applications are also provided in an environmentally benign way. Here, electricity, heat, and freshwater needed in a community consisting of 100 houses are provided. The costs of capital, fuel, operation, and maintenance are calculated and evaluated in detail. Furthermore, an environmental impact assessment is performed by comparing carbon monoxide, carbon dioxide, nitrogen oxides, sulfur dioxide, unburned hydrocarbons, and particulate matter. In closing, both energy and exergy efficiencies of hydrogen and natural gas mixture-based (NG-80% and H2-20%) integrated systems are calculated as 27.47% and 37.43%, respectively.
Keywords: Cost; Efficiency; Exergy; Emissions; Hydrogen; Natural Gas; Renewable Energy; GAS; Energy & Fuels; Engineering